FDI, technical efficiency and spillovers: Evidence from Indian automobile industry - Abhisek Sur; Amarendu Nandy (Cogent Economics & Finance, 2018)
Exchange rate volatility has been identified as one of the drivers of export diversification. Previous studies have assumed a symmetric relationship between the two variables. However, because volatility could be positive or negative and economic agents react to these changes differently, recent studies argue for the adoption of an asymmetric approach to the study of the relationship between the two variables. This study employed the partial sum process to create two variables to replace exchange rate volatility (Positive and negative variables) and utilized the Linear Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL) techniques to investigate asymmetric effects of exchange rate volatility on export diversification in Ghana for the period 1983 to 2015. The results indicate that exchange rate volatility has asymmetric relationship with export diversification in Ghana. The study revealed that other drivers of export diversification in Ghana are income, investment, infrastructure, openness, and inflation. The paper recommends that the Central Bank should strengthen its efforts at stabilizing the exchange value of the cedi.
Keywords: D24; F14; L62; 330; foreign direct investment; technical efficiency; spillover effect; stochastic frontier analysis; automobile industry; India